2020
DOI: 10.1177/2055116920906936
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic neuropathy in an acromegalic cat without concurrent diabetes mellitus

Abstract: Case summary A 17-year-old neutered male European Shorthair cat was presented owing to an inability to jump and respiratory stridor. The owner did not report any other clinical signs. On physical examination, the main findings were plantigrade stance, broad facial features and inspiratory stridor. Neurological examination revealed posterior paraparesis, hypotonia and right hindlimb muscle atrophy. Laboratory findings were unremarkable and glycaemia was normal. Serum insulin-like growth factor 1 concentration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…4,7,8 Sciatic neuropathy was confirmed by electrodiagnostic tests in one of these cats. 4 Of note, peripheral nerve dysfunction is a well-recognised complication of acromegaly in humans. 19 Around 5% of cats in the present study were not diabetic when diagnosed with HS and had not developed DM at the time the questionnaire was completed by the owners.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…4,7,8 Sciatic neuropathy was confirmed by electrodiagnostic tests in one of these cats. 4 Of note, peripheral nerve dysfunction is a well-recognised complication of acromegaly in humans. 19 Around 5% of cats in the present study were not diabetic when diagnosed with HS and had not developed DM at the time the questionnaire was completed by the owners.…”
Section: Discussionmentioning
confidence: 75%
“…5 Plantigrade stance in cats with HS is usually considered the consequence of diabetic neuropathy; however, it was described in one non-diabetic cat in the present study and previously reported in 3/5 non-diabetic cats with HS. 4,7,8 Sciatic neuropathy was confirmed by electrodiagnostic tests in one of these cats. 4 Of note, peripheral nerve dysfunction is a well-recognised complication of acromegaly in humans.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…23 Reports in cats about this issue are lacking, and only five cases with HST without DM have been published to date. [26][27][28] In a recent study on quality of life in cats with HST, another seven cases of acromegaly without DM were mentioned. 29 Two studies have indicated that the prevalence of hyperthyroidism in the population of diabetic cats is around 5-6%.…”
Section: Discussionmentioning
confidence: 99%